Pengaruh Macam Pupuk Bokashi Dan Dosis Pupuk Npk Terhadap Pertumbuhan Padi Merah (Oryza Nivara L.) Varietas Sembada merah - Evayulianti, Evayulianti; Darnawi, Darnawi; Maryani, Yekti; Heru Pamungkas, Djoko (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of the interaction between the administration of various types of fertilizer bokashi and NPK ponska fertilizer doses on the growth of red rice of the red sembada variety. Sedayu, Bantul, Special Region of Yogyakarta. The agro-climate of the land in the Sedayu area is a lowland area with an elevation of 88 meters above sea level (masl), the soil type is regosol, with a PH of 5.5-6.7. The maximum temperature in Sedayu District is 32.40°C and a minimum temperature of 24.50°C, rainfall is 1.654 mm/year.This study used a Completely Randomized Block Design (RAKL) with two treatment factors, namely: Facto I Giving different types of bokashi fertilizer, J1 Bokashi Straw 2.500 kg /ha ,J2 Bokashi Mushroom Waste 2.500 kg/ha, J3 Without Bokashi 2.500 kg/ha Factor II Dosage of NPK phonska fertilizer, P1 200 kg/ha P2 250 kg/ha, P3 300 kg/ha variable growth and yield variable. Growth variables include plant height, number of tillers, plant fresh weight and plant dry weight. Yield variables include the number of productive tillers, panicle length, 1000 grain weight and grain yield per hectare. Data were analyzed using variance at the 5% level followed by using Ducan's Multiple Test (DMRT) at a = 5% level. The results of the analysis of variance showed that there was no interaction between the type of bokashi fertilizer and the dosage of ponskar NPK fertilizer on the growth and yield of red rice plants. The treatment of giving various types of bokashi fertilizer with doses of ponskar NPK fertilizer did not significantly affect the growth and yield of red rice plants. The treatment of ponskar NPK concentration did not significantly affect the growth and yield of red rice plants